Credit management audit and the profitability of the Prisma Microfinance Savings and Credit Cooperative (2014-2017) - Guillen Sauñe, Milena (2020)
Objective: To determine how the credit management auditing has an impact on the profitability of the Prisma Microfinance Savings and Credit Cooperatives (COOPAC MFP). Method: The type of research is non-experimental, descriptive and explanatory. Primary source information was collected; it was obtained through surveys, interviews with credit and collection advisors and documentary and financial information about COOPAC MFP. Surveys, interviews with credit and collection advisors and documentary and financial information about COOPAC MFP were prepared. Results: It is evident that there is no good credit management in the recruitment of credit and collection personnel or in the evaluation processes for the granting of credit, nor supervision and monitoring of the risks and the overdue portfolio. Conclusions: There are no good practices of credit management auditing by credit and collection advisors, such as knowledge of credit policy and products to perform an evaluation, approval and recovery of credits, because they do not receive constant training; this creates a credit risk that has a negative impact on the profitability of the COOPAC MFP.